2021
DOI: 10.3389/fphys.2021.712649
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Artificial Intelligence in Poultry Processing and Classification Efficiencies of Different Classification Models in the Categorisation of Breast Fillet Myopathies

Abstract: Breast meat from modern fast-growing big birds is affected with myopathies such as woody breast (WB), white striping, and spaghetti meat (SM). The detection and separation of the myopathy-affected meat can be carried out at processing plants using technologies such as bioelectrical impedance analysis (BIA). However, BIA raw data from myopathy-affected breast meat are extremely complicated, especially because of the overlap of these myopathies in individual breast fillets and the human error associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 99 publications
(151 reference statements)
0
11
0
Order By: Relevance
“…SVM aims to discover a hyperplane that can separate two classes of provided data with a maximum margin while still offering the best generalization capability for a two-class linearly separable learning assignment. It provides highly accurate results on the training dataset and high predicting accuracy for the new dataset from the same population as the training dataset [ 30 ]. A detailed working principle for the SVM algorithm can be found in Siddique et al [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…SVM aims to discover a hyperplane that can separate two classes of provided data with a maximum margin while still offering the best generalization capability for a two-class linearly separable learning assignment. It provides highly accurate results on the training dataset and high predicting accuracy for the new dataset from the same population as the training dataset [ 30 ]. A detailed working principle for the SVM algorithm can be found in Siddique et al [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…It provides highly accurate results on the training dataset and high predicting accuracy for the new dataset from the same population as the training dataset [ 30 ]. A detailed working principle for the SVM algorithm can be found in Siddique et al [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wooden breast (WB) is a breast myopathy that has recently begun to occur in the pectoral muscles of broiler chickens at slaughter age. Wooden breast-affected filets are characterized by a dull appearance and tough texture ( 1 ). It has been reported that birds with wooden breast were even up to 79% ( 2 ), which implies chicken breast filets with low quality has become one of the major problems nowadays, and it has been estimated to cause annual economic losses up to one billion dollars worldwide ( 3 ).…”
Section: Introductionmentioning
confidence: 99%